The Photovoltaic Generation and its Energy Contribution and Demand Shifting at the Center Headquarters of the Federal University of Technology - Paraná - Campus Curitiba - Mariano,Juliana D’Angela (2018)
ABSTRACT Distributed photovoltaic (PV) generation is characterized by the application of several small power plants in urban centers. This form of energy deserves special mention due to the possibility of installation in existing areas such as roofs and facades. Thus, the implementation of these systems represents positive modifications of the urban scenario, with the adhesion of PV modules, presenting much smaller social and environmental impacts than that of large conventional plants. In this sense, this study aims at analyzing the demand and consumption curves of the Center headquarters buildings of Federal University of Technology - Paraná (UTFPR) in Curitiba, by applying the COPEL’s CAS Hemera platform, in order to determine the potential for implementation of grid-connected photovoltaic systems in this premise, because they allow the cost reductions in electric power. The first UTFPR’s grid-connected photovoltaic system was introduced in December 2011, at the Center’s headquarters, in one of the blocks of the university, which by the end of 2016 generated a total of 11.67 MWh of electricity. This paper proposes an expansion scenario for the existing grid-connected photovoltaic system, using the available coverage showing the shifting or reduction of energy demand peaks and the energy contribution to UTFPR's Center headquarters.